2009
DOI: 10.1002/poc.1522
|View full text |Cite
|
Sign up to set email alerts
|

The SN3–SN2 spectrum. Rate constants and product selectivities for solvolyses of benzenesulfonyl chlorides in aqueous alcohols

Abstract: Rate constants for a wide range of binary aqueous mixtures and product selectivities (S) in ethanol–water (EW) and methanol–water (MW) mixtures, are reported at 25 °C for solvolyses of benzenesulfonyl chloride and the 4‐chloro‐derivative. S is defined as follows using molar concentrations: S = ([ester product]/[acid product]) × ([water solvent]/[alcohol solvent]). Additional selectivity data are reported for solvolyses of 4‐Z‐substituted sulfonyl chlorides (Z = OMe, Me, H, Cl and NO2) in 2,2,2‐trifluoroethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 60 publications
3
37
1
Order By: Relevance
“…The kinetic isotope effect was examined and k(H 2 O)/k(D 2 O) values are calculated to be 1.64 (Z = MeO) and 1.97 (Z = O 2 N), respectively. They are somewhat larger than experimental values, 1.37 (Z = MeO) and 1.76 (Z = O 2 N) . The large difference indicates the different mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The kinetic isotope effect was examined and k(H 2 O)/k(D 2 O) values are calculated to be 1.64 (Z = MeO) and 1.97 (Z = O 2 N), respectively. They are somewhat larger than experimental values, 1.37 (Z = MeO) and 1.76 (Z = O 2 N) . The large difference indicates the different mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The distinction of these two phenomena is difficult . To clarify this issue, Bentley et al investigated the rate constants and product selectivities of the solvolyses of para‐Z‐benzenesulfonyl chlorides in aqueous alcohols; see Scheme b . They found that the reaction has a third‐order character when the EWG Z = O 2 N was used, indicating that the reaction proceeds with a termolecular process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In recent years, mechanistic studies of nucleophilic displacement reactions at the tetra-coordinate sulfur center have included intensive experimental 8,9,13,14 and theoretical 15 efforts due to the wide range of applications of such reactions in the synthesis of sulfur drugs. 19 S N 2-S N 1 and S N 3-S N 2 spectrum mechanisms were reported by Bentley et al 6,18 Recent theoretical calculations of a range of acetone-water mixtures have provided independent evidence of the S N 2-S N 1 spectrum of the mechanism involved in the solvolyses of substituted benzyl chlorides 17 as well as reports of S N 3-S N 2 spectrum mechanisms of the solvolysis of substituted benzenesulfonyl chlorides. Rogne and Lee favor S N 2, 7,9,17 whereas Ciuffarin favors an S A N (addition-elimination) mechanism.…”
mentioning
confidence: 81%
“…16 There is, however, a considerable amount of debate regarding the mechanism of action, i.e., whether it is an S N 2, 7,9,17 an S N 1-S N 2 and S N 2-S N 3 (Scheme 2), 6,18 or an S A N 19 process. 6,18 From mechanistic studies of the solvolysis of substituted benzyl chlorides, 8,18 carbamoyl chlorides, 22b,27 and substituted benzenesulfonyl chlorides, 6,7,9 Bentley et al 18 reported that the positioning within the mechanistic spectrum depends on the GW l value (Scheme 3). 19 S N 2-S N 1 and S N 3-S N 2 spectrum mechanisms were reported by Bentley et al 6,18 Recent theoretical calculations of a range of acetone-water mixtures have provided independent evidence of the S N 2-S N 1 spectrum of the mechanism involved in the solvolyses of substituted benzyl chlorides 17 as well as reports of S N 3-S N 2 spectrum mechanisms of the solvolysis of substituted benzenesulfonyl chlorides.…”
mentioning
confidence: 99%